ANALISIS TINGKAT KEPUASAN WISATAWAN TERHADAP KUALITAS PELAYANAN DI MBA TOUR & TRAVEL - Putu Putri Susanti; I Nyoman Sudiarta; I Made Kusuma Negara (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2016)
The purpose of this study was to determine the level of tourist satisfaction with services provided by the MBA Tour & Travel by analyzing the performance of employees and the results that the comparison of performance and the importances of the suitability to be used to determine priorities and scale repair services tourist satisfaction. The method used in this study was accidental sampling SPSS analysis which multiply 5 to 10 of the 15 indicators in order to get 75 respondents. The analysis technique used is quantitative descriptive analysis assisted by Likert scale with Cartesian diagram to determine the position of an indicator. The average data processing performance that is equal to 2.66 and the average of average importance rate of 3.47 with 77% of conformity was concluded that tourists feel quite satisfied with the services provided by the MBA Tour & Travel.